“Fair Play”: A Videogame Designed to Address Implicit Race Bias Through Active Perspective Taking - Gutierrez, Belinda (Games Health J, 2014)
Objective: Having diverse faculty in academic health centers will help diversify the healthcare workforce and reduce health disparities. Implicit race bias is one factor that contributes to the underrepresentation of Black faculty. We designed the videogame “Fair Play” in which players assume the role of a Black graduate student named Jamal Davis. As Jamal, players experience subtle race bias while completing “quests” to obtain a science degree. We hypothesized that participants randomly assigned to play the game would have greater empathy for Jamal and lower implicit race bias than participants randomized to read narrative text describing Jamal's experience. Materials and Methods: University of Wisconsin–Madison graduate students were recruited via e-mail and randomly assigned to play “Fair Play” or read narrative text through an online link. Upon completion, participants took an Implicit Association Test to measure implicit bias and answered survey questions assessing empathy toward Jamal and awareness of bias. Results: As hypothesized, gameplayers showed the least implicit bias but only when they also showed high empathy for Jamal (P=0.013). Gameplayers did not show greater empathy than text readers, and women in the text condition reported the greatest empathy for Jamal (P=0.008). However, high empathy only predicted lower levels of implicit bias among those who actively took Jamal's perspective through gameplay (P=0.014). Conclusions: A videogame in which players experience subtle race bias as a Black graduate student has the potential to reduce implicit bias, possibly because of a game's ability to foster empathy through active perspective taking.